Measuring emotions triggered by fragrance through behavioral paradigms - Yue Lv; Hua Sun; Hong-yu Wu; Kaiwen Xiong (Frontiers in Psychology)
IntoductionFragrance has a positive impact on various aspects of people’s emotions, experiences, and behaviors, such as product satisfaction, happiness, and comfort in daily life. While previous research has predominantly utilized physiological measurements or subjective evaluations, behavioral methods have been underexplored. This study aims to explore the measurement of emotional responses to fragrance through behavioral paradigms.MethodsIn a self-controlled experiment, participants were instructed to smell various fragrances and assessed their emotional changes before and after exposure using EEG, emotion scales, and behavioral paradigms.ResultsThe findings revealed that the emotional bias measured by the Go/No-go Association Task (GNAT) was consistent with the emotional valence results obtained from EEG measurements, and the trend of time perception measured by the time bisection task was consistent with the arousal index measured by EEG. After smelling the orange fragrance, the EEG valence of participants increased from 2.61 to 3.68 (p = 0.017), the d value increased from −0.66 to 0.21 (p = 0.071), the EEG arousal decreased from 0.97 to −0.30 (p = 0.092), and the temporal dilation value increased from 57.24 to 67.51 (p = 0.038).DiscussionThe results indicate that changes in emotional valence and arousal in response to fragrance can be effectively assessed through behavioral paradigms. These results contribute to the fragrance product development and provide insights for enhancing multisensory experiences.